Chinese associations with particular reference to the surname, province and district associations / Low Lai Sheong - Low , Lai Sheong (1976)
The purpose of this study was to gain some insight into the status and workings of Chinese associations at present as compared to the past. In this study, only the surname (tsung tsai), district and provincial associations (hui kuan) are considered. Chinese associations have existed for a long time and the oldest association established in Selangor dates back to 1865. This study is confined to those located in Kuala Lumpur. The data was collected by interviewing the secretaries of the associations. In this study, the secretaries of the 43 Chinese associations in Kuala Lumpur were interviewed to obtain information on several aspects of the associations. The aspects touched were to see whether Chinese associations have adapted to the times or not; present and past functions of the associations; membership characteristics; nature of leadership, financial status; nature of social mixing; available facilities and attempts if any to keep uo with the times.